THE RELATIONSHIP OF DIETARY PATTERNS, PHYSICAL ACTIVITY, AND SCREEN TIME WITH THE INCIDENCE OF OVERWEIGHT AMONG TODDLER AGED 24–59 MONTHS IN SUDIMARA PINANG HEALTH CENTER AREA, TANGERANG CITY - Zahra, Audia; Paramita, Farah; Supriyadi; Kurniawan, Agung; Sundjaya, Tonny (Ridwan Institute, 2025)
Background: Overweight in toddlers may further develop into obesity. The Sudimara Pinang Community Health Center area has the highest number of overweight toddlers in Tangerang City. This study aims to examine the relationship between dietary patterns, physical activity, screen time, and the incidence of overweight among toddlers aged 24-59 months in Sudimara Pinang area. Method : This study employed a quantitative approach with a cross-sectional study design. A total of 93 toddlers were purposively selected from the five integrated health posts with the highest number of overweight toddlers. Nutritional status was assessed using anthropometric measurements. Dietary patterns were measured with a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), Physical activity with the Early Year Physical Activity Questionnaire (EY-PAQ), and screen time with the Seven in Seven Screen Exposure Questionnaire. Result: The findings revealed a significant association between dietary pattern (p-value = 0.016), and between physical activity and overweight incidence (p-value = 0.000). However, no significant relationship was found between screen time and overweight (p-value = 0.523). Conclusion: Dietary patterns and physical activity were significantly associated with overweight among toddlers, whereas screen time showed no significant relationship. These findings highlight the need for comprehensive intervention programs in the area, focusing on promoting healthy eating and physical activity.